A randomized controlled trial to compare group motivational interviewing to very brief advice for the effectiveness of a workplace smoking cessation counseling intervention. Issue 4 (5th July 2020) - Caponnetto, Pasquale; Maglia, Marilena; Floresta, Daniele; Ledda, Caterina; Vitale, Ermanno; Polosa, Riccardo; Rapisarda, Venerando
Abstract: Background: Studies show that smokers have a lower work performance due to time spent smoking, increased fatigue perception and are more absent from work due to smoking-related diseases. The workplace could represent an important location to promote smoking cessation. Methods: This study is a multi-center, controlled trial for smoking cessation counseling at the participants' workplace, where 656 randomized participants received four sessions of group motivational interviewing or four sessions of very brief advice and were followed up for 52 weeks. Results: The Continuous Quit Rate (CQR) was higher for the smoking cessation counseling group than for the very brief advice group during weeks 9 to 12 (17.5% vs. 3.6%) weeks 9 to 24 (13.4% vs. 3.4%) and weeks 9 to 52 (10.3% vs. 3.1%). Conclusions: This study demonstrated that motivational interviewing is an efficacious smoking cessation approach for smokers at their workplace. The short-term and long-term cessation rate of the intervention of the smoking cessation counseling group exceeded that of very brief advice.